THE INSTALLMENT DASHBOARD CAMERA WILL NOT AFFECT YOUR PRIVACY: A STUDY IN KUDUS REGENCY, KUDUS - Fariska Jihan Setiyowati; Aldyla Shesara Naswa; Adissya Mega Christia, (INTERNATIONAL JOURNAL OF LAW, GOVERNMENT AND COMMUNICATION (IJLGC), 2024)
The dashboard camera has become a very important device for vehicles nowadays because it is used for audio and/or video recordings. Recordings produced by the dashboard camera includes important evidences such as the route used, the front road, the road behind and the cabin, and also the conversation in the car for some types. In the present era, not everyone supports the development of dashboard camera technology. One of the reasons is privacy. Some people feel overexposed by dashboard camera in private vehicles. Privacy belongs to the private law thus the consent of each person is very important. In fact, people in Kudus Regency alone still not familiar with dashboard camera. This shows that it is still a long way to proceed the legality of it but at the same time this development of technology must be adapted carefully. The approach method used in the study is normative juridical, a scientific research procedure that relies on scientific logic and is viewed from a normative perspective. The research method employed in this study is qualitative descriptive. This approach relies on references from a collection of data obtained from library studies, includes previous laws and research, and is based on the opinion of the public, especially in the Kudus Regency. The study aims to strengthen the understanding that dashboard camera will not affect people's privacy as long as the private law regulates it in accordance with justice, certainty and the usefulness also to ensure legally that dashboard camera can improve legal protection.